Effects of nitrogen fertilizer and elevated CO2 on dry matter production and yield of rice cultivars - Razzaque, MA; Haque, MM; Hamid, MA; Khaliq, QA; Solaiman, ARM (Bangladesh Journal of Agricultural Research, 2010)
A pot experiment was conducted at Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur during the year 2003 to find out the dry matter production and yield of rice cultivars under different nitrogen levels and growing conditions. Thirty-day old single seedlings were transplanted in pot and were placed in 3 growing conditions, such as i) Open top chamber (OTC) with elevated CO2 (570 ± 50 ppm), ii) OTC with ambient CO2 (360 ± 50 ppm), and iii) open field condition. The three nitrogen levels used were, i) control, ii) optimum dose, and iii) supra optimum dose. Three rice cultivars used in the experiment were, i) BRRI dhan 39, ii) Khashkani, and iii) Shakkarkhora. Rice yield and dry matter production respond significantly to different environments. Increasing atmospheric CO2 increased grain yield. Stem dry weight, leaf dry weight, leaf sheath dry weight and root dry weight were increased in elevated CO2 than ambient CO2 and field condition. BRRI dhan 39 gave highest yield (50.82 g/plant) at supra optimum N level in elevated CO2. Local variety gave similar result under elevated CO2 in optimum and supra optimum N levels. The lowest yield (15.09 g/plant) was produced by Shakkorkhora in field condition with no nitrogen application. Key Words: Nitrogen; elevated CO2; yield; dry matter. DOI: 10.3329/bjar.v34i2.5804 Bangladesh J. Agril. Res. 34(2): 313-322, June 2009